2010
DOI: 10.1002/dc.21497
|View full text |Cite
|
Sign up to set email alerts
|

The value of fine needle aspiration biopsy in the diagnosis and prognostic assessment of palpable breast lesions

Abstract: In recent years there appears to be a growing movement toward the use of core needle biopsy (CNB) over fine needle aspiration biopsy (FNAB) for the detection of breast carcinoma. This tendency is caused in part by the idea that CNB can provide a more specific or definitive diagnosis as well as the belief that the assessment of prognostic/predictive factor is not possible or reliable on cytologic specimens. At our institution, FNAB of breast has been practiced for over 25 years with excellent cytologic-histolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
61
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 30 publications
6
61
1
Order By: Relevance
“…Bukhari and Akhtar [21] and Bukhari et al [8] found 11.42 % and 8.4% suspicious cell for malignancy respectively. 139 (9%) cases were atypical/suspicious for malignancy reported by Rosa et al [22] and 51 (3.3%) atypical by Yeoh and Chan [23]. Cytologic atypia comprises nuclear pleomorphism, loss of cohesiveness, irregular nuclear contours, irregular chromatin pattern, hyperchromasia, and high nuclear/cytoplasmic ratio.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Bukhari and Akhtar [21] and Bukhari et al [8] found 11.42 % and 8.4% suspicious cell for malignancy respectively. 139 (9%) cases were atypical/suspicious for malignancy reported by Rosa et al [22] and 51 (3.3%) atypical by Yeoh and Chan [23]. Cytologic atypia comprises nuclear pleomorphism, loss of cohesiveness, irregular nuclear contours, irregular chromatin pattern, hyperchromasia, and high nuclear/cytoplasmic ratio.…”
Section: Discussionmentioning
confidence: 95%
“…Bukhari et al [8] reported 20% inadequacy and reduced the number by repeating up to twice. Insufficient cases require re-evaluation of clinical and radiological findings as well as adequate follow-up, mostly in cases of palpable breast abnormalities [22].…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis and treatment, besides being life-saving, reduces morbidity (1). Various examinations, interventions or their combinations are used for early diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, breast FNA has a significant role in the evaluation of breast lumps however the success of breast FNA depends immensely upon correct preparation of cytological smears and skills of the person performing the procedure [13][14][15] which can ultimately lead to diagnostic failure. 16 Liquid based smears are better than the conventional cytological preparations since they avoid limiting factors such as obscuring material, airdried artifacts and irregular thickness of the smears.…”
Section: Discussionmentioning
confidence: 99%